Examining the influence of media system dependency relations on user satisfaction, and continuance intention in social networking services - Ma, Chenwei; Zainudin, Sharifah Sofiah Syed; Abas, Wan Anita Wan; Feng, Sijing; Jin, Dian (RedFame Publishing, 2023)
Social Networking Services (SNS) exert a substantial influence in the digital realm. For marketers and entrepreneurs, comprehending the nuances of potential consumer interaction with SNS is pivotal to craft optimal communication strategies. Consequently, deciphering the determinants that either encourage or hinder individual SNS usage behaviors becomes imperative, as it fosters deeper insights into users' continuance intentions and facilitates the building of robust relationships. Drawing upon the Media System Dependency (MSD) theory, this research addresses two main questions: 1) How do individuals' MSD relations, encompassing Understanding Dependency (UD), Orientation Dependency (OD), and Play Dependency (PD), satisfaction (ST) within the SNS context? 2) Does satisfaction subsequently enhance their continuance intention (CI) towards the SNS? To address these queries, we scrutinized data amassed from 393 online Weibo users in China. Participants, all of whom possessed prior Weibo experience, were invited to partake in a comprehensive survey. The proposed hypotheses were rigorously examined using Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis revealed that the three delineated MSD relations significantly bolstered participants' ST, which in turn robustly influenced their CI. This study's findings shed invaluable light on the nexus between MSD relations and SNS engagement, offering meaningful implications for both academics and SNS practitioners. Future research endeavors are encouraged to expand upon these insights and further fortify our understanding of the topic.